Folding kinetics of the outer membrane proteins OmpA and FomA into phospholipid bilayers - Kleinschmidt, Jörg (My University, 2006)
The folding mechanism of outer membrane proteins (OMPs) of Gram-negative bacteria into lipid bilayers has been studied using OmpA of E.coli and FomA of F.nucleatum as examples. Both, OmpA and FomA are soluble in unfolded form in urea and insert and fold into phospholipid bilayers upon strong dilution of the denaturant urea. OmpAis a structural protein and forms a small ion channel, composed of an 8-stranded transmembrane β-barrel domain. FomA is a voltage-dependent porin, predicted to form a 14 stranded β-barrel. Both OMPs fold into a range of model membranes of very different phospholipid compositions. Three membrane-bound folding intermediates of OmpA were discovered in folding studies with dioleoylphosphatidylcholine bilayers that demonstrated a highly synchronized mechanism of secondary and tertiary structure formation of β-barrel membrane proteins. A study on FomA folding into lipid bilayers indicated the presence of parallel folding pathways for OMPs with larger transmembrane β-barrels.
Keywords: Membrane protein folding; Outer membrane proteins; OmpA; FomA; Membrane protein chaperones; 570